Droplet digital PCR detection and next-generation sequencing of HIV-1 in breastmilk of breastfeeding women on antiretroviral treatment - Hurree, Jennah Nivashni (Department of Pathology, 2025)
Persistence of HIV-1 in a stable latent reservoir in breastmilk has been associated with low- level mother to child transmission despite maternal antiretroviral therapy (ART). We aimed to evaluate and optimize the sensitivity of HIV-1 DNA quantitation in breastmilk using droplet digital PCR (ddPCR) and sequencing of viral variants in breastmilk using Illumina MiSeq next generation sequencing to inform transmission risk and efficacy of maternal ART clinical trials. HIV-negative breastmilk samples were spiked with 8E5 cells (a cell line where each cell contains one replication-defective HIV genome) at concentrations ranging from 10 000 - 1 8E5 cell(s)/million. Genomic DNA was extracted with the QIAGEN AllPrep DNA/RNA Mini Kit (QIAGEN, Hilden, Denmark) and ddPCR was performed using the ddPCR Supermix for Probes (No dUTP) (BIO-RAD, California, USA), HIV-1 gag and/or pol and housekeeping gene rpp30 primers and probes, BanII restriction enzyme, CutSmart buffer (New England Biolabs, Massachusetts, USA) and the QX200TM ddPCR System (BIO-RAD, California, USA). The envelope gene V1-V2 region was amplified using the KAPA2G Fast Multiplex Mix (Roche, Basel, Switzerland) and Expand High Fidelity PCR enzyme (Roche diagnostics, Basel Switzerland) with Nextera DNA CD indexes and sequenced via the Illumina Miseq v3 platform. Genomic DNA recovery was low (ranging from 25.12 - 106.85 ng/µl with an average of 67.18 ng/µl) when spiking in a background of 1 million cells, resulting in HIV DNA being detectable by ddPCR only in samples spiked with the highest 8E5 cell concentration. When repeating this experiment with 8E5 cell spike-in concentrations ranging from 50 000 - 5 8E5 cells/million in a total of 5 million cells, genomic DNA recovery was higher (ranging from 498.99 - 757.28 ng/µl with an average of 631.32 ng/µl) resulting in a detection sensitivity of 44.3 gag copies/million cells with a lowest per reaction HIV copy number detection of 7 gag copies. We noted that 8E5 cell line HIV genome copies/cell varied across different passages, ranging from 0.4 - 0.8 copies/cell instead of the expected 1 copy/cell. HIV-negative breastmilk samples spiked with 8E5 cells ranging from 50 000 - 50 8E5 cells/million were likewise successfully PCR amplified and sequenced (gDNA input at 1000 ng), with sequences matching the 8E5 HIV-1 /LAV genome, as expected. Additionally, this method was successfully applied to genomic DNA from PBMCs of women on ART from the CAPRISA 002 cohort, Kwa-Zulu Natal, confirming the sensitivity of this method to amplify low-copy number HIV templates. ddPCR and Illumina MiSeq methods were applied to cells from 2 ml breastmilk samples from three women with blood viral loads of 20 - 331 copies/ml from the Dolutegravir in pregnant HIV infected mothers and their neonates (DolPHIN-2) trial, yet no HIV genome copies above background level were detected and no HIV targets could be PCR amplified. Viral quantification and sequencing from breastmilk is difficult particularly when viral load is low in the presence of ART and no guidelines have been established for processing breastmilk. Both ddPCR and Illumina Miseq were successful at quantifying and sequencing low levels (1.3log10) of HIV from spiked-in breastmilk samples. HIV copies below background levels obtained from breastmilk samples of the DolPHIN-2 study potentially demonstrate effective viral suppression in breastmilk by integrase inhibitor Dolutegravir-based ART. However, the number of samples analysed was low and cell pellets available for analysis possibly contained too few cells for ddPCR detection and Illumina Miseq of HIV, based on our observations from the spike-in experiments.